Cuentas por cobrar del Comercial Regulito en la vía Babahoyo – Jujan durante el periodo 2022-2023. - Bajaña Villacrés, Paul Abraham (2024)
This case study focuses on the analysis of the accounts receivable of Comercial Regulito, a family business located on the Babahoyo - Jujan road, whose main activity is the wholesale of cereals, especially rice. Since its founding in 2003, the business has experienced steady growth and has positioned itself as a relevant player in the sector. However, during the 2022-2023 period, a worrying increase in accounts receivable was observed. This phenomenon is due, in part, to the lack of clear credit policies and ineffective control of credit transactions. Comercial Regulito's clients have been delaying their payments, thus increasing the overdue portfolio, which has a negative impact on the company's cash flow. This study focuses on identifying the underlying causes of this situation, evaluating the current management of accounts receivable. Through a comprehensive analysis of financial data for the period in question, we seek to understand current collection practices and determine how delinquency relates to the financial health of the company. In addition, collection strategies are reviewed, and the deficiencies that have led to the increase in accounts receivable are analyzed. By addressing problems such as delinquency, lack of policies and lack of records of all accounts, we can note that, with proper management, Comercial Regulito can turn these challenges into an opportunity to strengthen its financial operations and consolidate its future growth. In conclusion, this case study highlights the current challenges faced by Comercial Regulito.